Changes in the Deep Western Boundary Current at 53°N - Kulan, Nilgun; Myers, Paul G. (2012)
Southward transports in the deep western boundary current across 53°N, over 1949–99, are determined from a historical reconstruction. Long-term mean transports, for given water masses, for net southward transport (the southward component of the transport not including recirculation given in parentheses) are 4.7 ± 2.3 Sv (5.1 ± 2.4 Sv) (Sv ≡ 106 m3 s−1) for the Denmark Strait Overflow Water, 6.1 ± 2.7 Sv (6.8 ± 1.7 Sv) for the Iceland–Scotland Overflow Water, 6.5 ± 2.6 Sv (7.1 ± 1.8 Sv) for classical Labrador Sea Water, and 2.3 ± 1.9 Sv (2.7 ± 3.4 Sv) for upper Labrador Sea Water. The estimates take into account seasonal and interannual variability of the isopycnal positions and suggest the importance of including this factor. A strong correlation, 0.91, is found between variability of the total and baroclinic transports (with the barotropic velocity removed) at the annual time scale. This correlation drops to 0.32 if the baroclinic transports are, instead, computed based upon the use of a fixed level of no motion at 1400 m. The Labrador Sea Water layer shows significant variability and enhanced transport during the 1990s but no trend. The deeper layers do show a declining (but nonstatistically significant) trend over the period analyzed, largest in the ISOW layer. The Iceland–Scotland Overflow Water presents a 0.029 Sv yr−1 decline or 1.5 Sv over the 50-yr period, an 18%–22% decrease in its mean transport.